A Numerical Solution for the Shape of Fabric-formed Concrete Structures. (November 2016) - Foster, Robert M.; Ibell, Tim J.
Abstract: This paper details a new numerical method for determining the form of a section of flexible, impermeable and inextensible hanging fabric subject to the hydrostatic load imposed by wet concrete. A closed form solution is already known to exist in the form of incomplete elliptic integrals, but this can be difficult to implement in practice. The numerical method presented here was developed by the authors, and the method has been subsequently implemented by researchers investigating the behaviour of fabric-formed concrete beams. It is thought that this method may be of use to other designers and investigators interested in the form of flexible formworks and also of wider interest for the design of flexible scoops or other hydrostatically loaded structures. The method is shown to be applicable to full, part-full and overfull, i.e. surcharged, containers. The method's accuracy is demonstrated by comparison with the predictions of the closed form solution and with reference to the conclusions of previous empirical investigations. Comparison is also made on a graphical basis to a number of reported hydrostatically determined forms, with good agreement being shown. This indicates that the approach has direct application as a form-finding procedure for fabric-formed concrete structures.